Comparative Analysis of Futures Option Characteristics in Spot and Futures Markets Between Asia and Europe: Validation of Put-Call Parity and the Role of Market Volatility - Thomas Nadeak; Toni Heryana; Wahyudayanto Utama; H. Nugraha; Maya Sari (Westscience Press, 2025)
This study aims to analyze the development of research related to “futures options” using a bibliometric approach based on Scopus data with the keyword “futures options,” covering 280 journal articles for the period 1973-2024. The analysis was conducted using Biblioshiny in R-Studio for bibliometrics and VOSviewer for keyword network visualization. Results showed that dominant themes included implied volatility, stochastic volatility, and price dynamics with a focus on hedging strategies, risk, and derivatives market dynamics. The network visualization revealed modern themes such as sustainability and climate change, indicating the potential integration of these financial instruments with global sustainability issues. Inter-author collaboration was high, averaging 2.22 authors per document, with 22.5% of documents involving international authors. The study also noted high relevance with the average citations per document reaching 24.81 and an annual growth rate of 2.76%. Temporal analysis showed a significant increase since the 1980s, a peak in 2010-2020, and a decline in 2020-2024, influenced by shifts in research focus or the impact of the COVID-19 pandemic. Visualization through VOSviewer identified five main clusters, with implied volatility having strong connections to hedging and stochastic volatility, while new themes such as sustainability are still in the early stages of exploration. The study concludes that while the futures options theme is mature, there are opportunities for exploration in lesser explored topics such as the integration of sustainability issues and cross-regional analysis, providing a comprehensive picture of the research landscape and future directions.